2012
DOI: 10.1007/s11910-012-0310-7
|View full text |Cite
|
Sign up to set email alerts
|

Using Pictures and Words To Understand Recognition Memory Deterioration in Amnestic Mild Cognitive Impairment and Alzheimer's Disease: A Review

Abstract: Difficulty recognizing previously encountered stimuli is one of the earliest signs of incipient Alzheimer’s disease (AD). Work over the last 10 years has focused on how patients with AD and those in the prodromal stage of amnestic mild cognitive impairment (aMCI) make recognition decisions for visual and verbal stimuli. Interestingly, both groups of patients demonstrate markedly better memory for pictures over words, to a degree that is significantly greater in magnitude than their healthy older counterparts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 92 publications
4
27
0
8
Order By: Relevance
“…However, there is also evidence that familiarity performance—even when measured in the same individuals in the same manner—can vary according to the stimulus dimensions that are most relevant and/or salient during a particular task. For example, Embree, Budson, and Ally (2012) found that familiarity in a group of patients with MCI was intact for pictures, but impaired for words, a finding that roughly mirrors the general pattern in the literature (for review, see Ally, 2012). In addition, a patient with a left perirhinal cortex lesion who was initially characterized as having a general familiarity deficit (Bowles et al, 2007) was recently found to have intact familiarity for nonverbal stimuli, such as faces and abstract line drawings (Martin, Bowles, Mirsattari, & Köhler, 2011).…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…However, there is also evidence that familiarity performance—even when measured in the same individuals in the same manner—can vary according to the stimulus dimensions that are most relevant and/or salient during a particular task. For example, Embree, Budson, and Ally (2012) found that familiarity in a group of patients with MCI was intact for pictures, but impaired for words, a finding that roughly mirrors the general pattern in the literature (for review, see Ally, 2012). In addition, a patient with a left perirhinal cortex lesion who was initially characterized as having a general familiarity deficit (Bowles et al, 2007) was recently found to have intact familiarity for nonverbal stimuli, such as faces and abstract line drawings (Martin, Bowles, Mirsattari, & Köhler, 2011).…”
Section: Introductionmentioning
confidence: 52%
“…Thus, this form of perceptual fluency, as well as the inferential processes that allow this fluency to be experienced as familiarity, may be spared in some patients with memory disorders (but see Algarabel, Escudero, et al, 2009). By contrast, impairments in familiarity in such patients have most often been found under conditions that emphasize conceptual processing (e.g., Ally, 2012; Embree et al, 2012). Perhaps impoverished conceptual stimulus processing due to atrophy of anterior temporal regions can contribute to deficits in the use of conceptual information to discriminate between studied and unstudied items, even when the ability to use perceptual information in this manner remains unaffected.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, as discussed above, this conclusion cannot be verified here because patients may fail to create an integrated perceptual and conceptual representation of the item-color conjunction before it is available for familiarity-related memory processes. More generally, it is likely that contradictory evidence regarding the integrity of familiarity in the course of Alzheimer's disease arises because of the influence of various task-related or patient-related factors, such as the intrinsic properties of the methods used to estimate recollection and familiarity (Wolk et al, 2008), the extent to which memory decisions benefit from the use of processing fluency (Ally, 2012; Bastin, Willems, Genon, & Salmon, 2013), or the severity and nature of patients' cognitive deficits (e.g., Bastin, Willems, et al, 2013; Hoppstadter et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…24,25 A concept version of the MIBBO met the aim and conditions as described above and was tested in preliminary pilots. Through an iterative process, the measure was improved, resulting in a final version presented in Table 2.…”
Section: Measurementioning
confidence: 99%